A dual functional redox enzyme maturation protein for respiratory and assimilatory nitrate reductases in bacteria. Issue 6 (6th April 2019) - Pinchbeck, Benjamin J.; Soriano‐Laguna, Manuel J.; Sullivan, Matthew J.; Luque‐Almagro, Victor M.; Rowley, Gary; Ferguson, Stuart J.; Roldán, M. Dolores; Richardson, David J.; Gates, Andrew J.
Summary: Nitrate is available to microbes in many environments due to sustained use of inorganic fertilizers on agricultural soils and many bacterial and archaeal lineages have the capacity to express respiratory (Nar) and assimilatory (Nas) nitrate reductases to utilize this abundant respiratory substrate and nutrient for growth. Here, we show that in the denitrifying bacterium Paracoccus denitrificans, NarJ serves as a chaperone for both the anaerobic respiratory nitrate reductase (NarG) and the assimilatory nitrate reductase (NasC), the latter of which is active during both aerobic and anaerobic nitrate assimilation. Bioinformatic analysis suggests that the potential for this previously unrecognized role for NarJ in functional maturation of other cytoplasmic molybdenum‐dependent nitrate reductases may be phylogenetically widespread as many bacteria contain both Nar and Nas systems. Abstract : Redox enzymes for respiratory and assimilatory nitrate reduction are ubiquitous in microorganisms. Expression of redox enzyme maturation proteins are essential for respiratory and assimilatory nitrate reduction. One such maturation protein NarJ was previously thought to mature only the respiratory nitrate reductase, but this present study reveals that it has an essential dual role in functional maturation of the assimilatory nitrate reductase.